2015
DOI: 10.1136/archdischild-2015-309015
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial response to hypoxia in survivors of chronic lung disease of prematurity

Abstract: Children who had CLD in infancy had increased pulmonary arterial reactivity during hypoxia, thus long-term follow-up is warranted in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
1
0
2
Order By: Relevance
“…Relationships between EP status and cardiovascular function persist in this new evaluation at 19 years, but significant differences between the EP and control groups are still not evident in peripheral blood pressure, whereas our central blood pressure and augmentation pressure data show significant differences. At 11 years we postulated that augmentation pressure differences represented alterations in the smaller pre-resistance and resistance vessels and confirm this here, consistent with described alterations in the pulmonary arteries following neonatal BPD 25 . Further work is required to understand the mechanisms of hypertension following EP birth in order to manage this optimally.…”
Section: Discussionsupporting
confidence: 90%
“…Relationships between EP status and cardiovascular function persist in this new evaluation at 19 years, but significant differences between the EP and control groups are still not evident in peripheral blood pressure, whereas our central blood pressure and augmentation pressure data show significant differences. At 11 years we postulated that augmentation pressure differences represented alterations in the smaller pre-resistance and resistance vessels and confirm this here, consistent with described alterations in the pulmonary arteries following neonatal BPD 25 . Further work is required to understand the mechanisms of hypertension following EP birth in order to manage this optimally.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests a primary vascular injury that may occur in some extremely preterm infants, independent of lung disease. We reported that children aged 8–12 years who had BPD had normal myocardial function and responses to hypoxia but had increased pulmonary arterial stiffness during hypoxia . Children who had BPD have increased pulmonary vascular reactivity to hypoxia thus may be at risk of developing pulmonary hypertension at an earlier age compared to healthy preterm infants despite normal cardiovascular function at rest during normoxia.…”
Section: Discussionmentioning
confidence: 98%
“…Nach neonatalem Lungenversagen und insbesondere nach einer ECMO-Therapie können verschiedenste Langzeitmorbiditäten auftreten, die die Entwicklung dieser Kinder lebenslang beeinträchtigen [1][2][3][4][5][6]. Die Evaluation des Langzeitverlaufs dieser schwer kranken Neugeborenen ist als Qualitätskriterium für ein ECMO-Zentrum unverzichtbar [7] und sie besitzt einen hohen Stellenwert in der Beratung von Eltern.…”
Section: Einführungunclassified
“…So berichten Russell et al von muskuloskeletalen Auffälligkeiten nach Zwerchfellhernienkorrekturoperation [5]. Auch reagieren ihre pulmonalen Gefäße empfindlich auf eine Hypoxie [4]. Des weiteren beschreiben Patridge et al, dass 30 % ihrer Patienten nach CDH-OP an einer Hörstörung leiden [3].…”
Section: Diskussionunclassified